About teachers’ formation and the role of classics in art classes: beauty can be everywhere (Palíndromo, 2022)
This paper aims to discuss the idea of “classics” in Art teaching, from the complex perspective that put this concept either as the core of the educational processes, or either as a to-be-avoided conception. The objective is to put face-to-face different conceptions of the use of “classics” in the educational processes of Art, a main issue in the researches related to Art teachers’ formation that are conducted in the Observatório da Formação de Professores no âmbito do Ensino de Arte (OFPEA/BRARG). Bibliographic research was the chosen methodological path, going over both traditional and contemporary Art teaching authors. The idea is to better understand the criteria that define what undoubtedly is considered “Classic”, as paintings, compositions, romances, dramas, and how that conception is assumed by Art teachers. In particular it is intended to understand what defines the stability and resistance of certain Art works as “classics” (SAVIANI, 2013); or what defines art works as unforgettable through aspects that pass-through times and cultures (CALVINO, 2007)The results intend to highlight the mistakes on summarily repel the “classics” in Art teaching, with the damage of deny to the students the essential relations that they could build with Art through the “classics”.
Keywords: Art teaching; Teachers’ formation; Classics